2018
DOI: 10.3390/ncrna4040043
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs Associated with Heterochromatin Function in Immune Cells in Psychosis

Abstract: Psychosis is associated with chronic immune dysregulation. Many long non-coding RNAs (lncRNAs) display abnormal expression during activation of immune responses, and play a role in heterochromatic regulation of gene promoters. We have measured lncRNAs MEG3, PINT and GAS5, selected for their previously described association with heterochromatin. Peripheral blood mononuclear cells (PBMCs) were isolated from blood samples collected from 86 participants with a diagnosis of psychosis and 44 control participants. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…these transcripts has been associated with PANSS score (17). Moreover, clinical diagnoses of psychosis and symptom severity have been shown to alter expression of a number of lncRNAs (22) indicating a substantial role for these transcripts in the pathogenesis of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…these transcripts has been associated with PANSS score (17). Moreover, clinical diagnoses of psychosis and symptom severity have been shown to alter expression of a number of lncRNAs (22) indicating a substantial role for these transcripts in the pathogenesis of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…They reported diagnostic differences with MEG3, PINT, and GAS5, and symptom acuity effect with MEG3 and GAS5. Moreover, there was significant difference in the expression of MEG3 between drug naïve patients and patients received risperidone (22). IFNG-AS1 expression has been shown to be down-regulated in patients with schizophrenia compared with healthy subjects in correlation with IFNG expression indicating a putative role for inflammation in this disorder (23).…”
Section: Lncrna Profile In Peripheral Bloodmentioning
confidence: 98%
“…Furthermore, increasing numbers of studies have shown that the levels of lncRNA in breast cancer tissues are imbalanced, including molecules such as zinc finger E‐box binding homeobox 1 (ZEB1)‐AS1 17,18 . Th lncRNAs regulate a variety of cellular functions, disorders of which are often associated with human diseases, including cancer 19,20 …”
Section: Introductionmentioning
confidence: 99%
“…17,18 Th lncRNAs regulate a variety of cellular functions, disorders of which are often associated with human diseases, including cancer. 19,20 For example, TTN-AS1 has been identified as a novel lncRNA with previously published studies suggesting that TTN-AS1 is an oncogene in multiple cancers, for instance, hepatocellular carcinoma, cervical cancer, papillary thyroid cancer, and gastric cancer. 21,22 Cui et al 23 established that TTN-AS1 drives papillary thyroid carcinoma progression by regulation of the microRNA (miRNA)-153-3p/ZNRF2 axis and activation of the PI3K/Akt/mTOR pathway.…”
mentioning
confidence: 96%
“…Tan et al showed that Meg3 modulated AMPA Receptor expression in the primary cortical neuron surface ( 50 ). The expression of MEG3 in immune cells was reported to be differentially expressed in drug naïve psychosis patients compared to those treated with risperidone ( 51 ). A study using an Alzheimer's disease rat model reported that upregulation of MEG3 improved cognitive impairment and alleviates neuronal damage through inactivating the PI3K/Akt signaling pathway ( 52 ).…”
Section: Discussionmentioning
confidence: 99%